The Effect of Cooling on Driven Kink Oscillations of Coronal Loops - Nelson, Chris J.; Shukhobodskiy, Alexander A.; Erdélyi, Robertus; Mathioudakis, Mihalis (Frontiers in Astronomy and Space Sciences, 2019)
Ever since their detection two decades ago, standing kink oscillations in coronal loops have been extensively studied both observationally and theoretically. Almost all driven coronal loop oscillations (e.g., by flares) are observed to damp through time often with Gaussian or exponential profiles. Intriguingly, however, it has been shown theoretically that the amplitudes of some oscillations could be modified from Gaussian or exponential profiles if cooling is present in the coronal loop systems. Indeed, in some cases the oscillation amplitude can even increase through time. In this article, we analyse a flare-driven coronal loop oscillation observed by the Solar Dynamics Observatory's {\it Atmospheric Imaging Assembly} (SDO/AIA) in order to investigate whether {\color{red} models} of cooling can {\color{red} explain} the amplitude profile of the oscillation and {\color{red} whether hints of cooling can be found} in the intensity evolution of several SDO/AIA filters. During the oscillation of this loop system, the kink mode amplitude appears to differ from a typical Gaussian or exponential profile with some hints being present that the amplitude increases. The application of cooling coronal loop modelling allowed us to estimate the density ratio between the loop and the background plasma, with a ratio of between $2.05$-$2.35$ being returned. Overall, our results indicate that consideration of the thermal evolution of coronal loop systems can allow us to better describe oscillations in these structures and return more accurate estimates of the physical properties of the loops (e.g., density, scale height, magnetic field strength).